Comprehensive analysis of global research on overactive bladder: A scientometric approach - Wang, Lu; Deng, Sheng; Meng, Fanchao; Zhang, Lun; Min, Zhenxing; Li, Jitao; Wang, Jisheng (Frontiers in Surgery, 2023)
Background: Overactive bladder, a syndrome marked by an urgent need to urinate, is a globally prevalent ailment. Human health and quality of life are seriously affected. Therefore, it is essential to investigate the current progress and trends in this field. Objective: No bibliometric analysis of overactive bladder has been conducted. Through the use of bibliometrics and visualization, this study intends to examine the current progress and development trend of this field. Methods: Global publications on overactive bladder between January 2004 and August 2022 were extracted from the Web of Science core collection database. A bibliometric and visual analysis was carried out using VOSviewer software and CiteSpace. Results: Over the last 20 years, publications have grown rapidly, but after 2019, they started to fall. According to the collaboration network, the United States, Univ Pittsburgh AND NEUROUROLOGY AND URODYNAMICS are the most active countries, institutes AND journals in the field, respectively. All keywords were categorized by the symbiosis analysis into four categories: experimental study, symptoms, clinical use, and quality of life. The most prevalent keyword across all clusters is "overactive bladder." Conclusion: Year after year, there have been more publications in the field of overactive bladder research in many countries, and there has been a deeper level of cooperation and exchange. Researchers will still be interested in overactive bladder in the future. Currently, the clinical application of the disease and the safety and effectiveness of medications are being investigated. However, radical innovation in relevant experimental technologies is a significant obstacle in this field.